Nowy dokument historyczny - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
Methodology of New Film History The article’s author, based on various examples taken from the European documentary tradition, seeks to determine how the particular position of a new generation of found footage films is allocated and viewed in Polish cinemas and in relation to Polish contemporary audiovisual culture. Marek Hendrykowski redefines film editing (found footage film, compilation) as a historical narrative with its own, attractive poetics and successful way of negotiating its prestige and popularity in the public sphere.